Infantry tactical level combat training monitor system using ICT technology - Liem, Nguyen Huy; Hung, Truong Quoc; Anh, Tran Hai; Nguyên, Nguyen The; Trang, Dang Le Dinh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
Traditionally, the monitoring, adjusting, and evaluating of combat training in the Vietnamese army are conducted without any support equipment. The commander can only observe directly, memorize and shorthand to evaluate the training process, so learning from experience encounters certain difficulties. From that practical need, we develop an infantry division combat training monitor system based on information and communication technology (ICT). In the proposed system, various types of sensors were connected to collect several information from the battlefield. The data is analyzed to provide multiple points of view about combat training in real-time as well as after the practice. Thereby, the system not only helps commanders to build training plans based on 2D digital maps, monitor the training progress of infantry detachments through sensors, but also view the review, evaluate, review, draw experience after each exercise, help officers and soldiers recognize advantages and disadvantages, easily overcome, improve the quality of training and learning.